MRT letter: Localization of endogenous hydrogen peroxide by modified processes of sample preparation for transmissionelectron microscope in Escherichia coli. Issue 2 (15th November 2012) - Li, Xin; Hu, Rongliu; Zhu, Wenxue; Fan, Jinling; Pang, Xinyue; Wang, Na; Wang, Liping; Yang, Lipeng; Zhao, Chunyan; He, Chenyang
Abstract The bacterial endogenous hydrogen peroxide (H2O2) was detected cytochemically by its reaction with cerium chloride (CeCl3) to produce electron‐dense deposits of cerium perhydroxides. The sequence of fixation and CeCl3 staining of H2O2 in the processing of transmission electron microscope (TEM) sample preparation is crucial to the localization of endogenous H2O2 in Escherichia coli. In this study, results confirmed that the process that fixation simultaneously with CeCl3 staining provided optimum effects for H2O2 localization in E. coli. The modified process of TEM provides very efficient protection for H2O2 localization and more accurate quantization for the H2O2 accumulation in bacterial cells. Microsc. Res. Tech., 2013. © 2012 Wiley Periodicals, Inc.